Intertwining Beauty and Piety: Cosmetics, Beauty Treatments, and Ḥalāl Lifestyle in Urban Indonesia - Yanwar Pribadi; Muhammad Adlin Sila (Universitas Islam Negeri Mataram, 2023)
This article discusses the intertwinement of beauty and piety among middle-class Muslim women in urban Indonesia through the use of cosmetics and beauty treatments within the broader trends of ḥalāl lifestyle. It uses an anthropological approach with case studies in Jakarta, the capital city of Indonesia, and Serang, the capital city of Banten Province. Jakarta and Serang were chosen because Jakarta is a picture-perfect example of an older area characterized by the abundance of middle-class Muslims and the vehemence of ḥalāl lifestyle, while Serang represents a newer area in this regard. Moreover, this article explores the understanding and practices of religious rituals, as well as the responses of urban middle-class Muslim women towards commodified goods and services, consumerism behavior, and communal piety. We argue that the use of cosmetics and beauty treatments has become one of the most glaring public expressions that has concurrently influenced the way urban middle-class Muslim women perceive themselves, beauty, and piety. In addition, we contend that the understanding and practices of beauty and piety are becoming increasingly complex in urban areas. Finally, we maintain that ḥalāl lifestyle has played an important role in strengthening Islamic identity in contemporary Indonesia.